4-Isopropyl-2,6-bis(1-phenylethyl)aniline 1, an Analogue of KTH-13 Isolated from Cordyceps bassiana, Inhibits the NF-κB-Mediated Inflammatory Response - Woo Seok Yang; Zubair Ahmed Ratan; Gihyeon Kim; Yunmi Lee; Mi-Yeon Kim; Jong-Hoon Kim; Jae Youl Cho (Hindawi Limited, 2015)
The Cordyceps species has been a good source of compounds with anticancer and anti-inflammatory activities. Recently, we reported a novel compound (4-isopropyl-2,6-bis(1-phenylethyl)phenol, KTH-13) with anticancer activity isolated from Cordyceps bassiana and created several derivatives to increase its pharmacological activity. In this study, we tested one of the KTH-013 derivatives, 4-isopropyl-2,6-bis(1-phenylethyl)aniline 1 (KTH-13-AD1), with regard to anti-inflammatory activity under macrophage-mediated inflammatory conditions. KTH-13-AD1 clearly suppressed the production of nitric oxide (NO) and reactive oxygen species (ROS) in lipopolysaccharide (LPS) and sodium nitroprusside- (SNP-) treated macrophage-like cells (RAW264.7 cells). Similarly, this compound also reduced mRNA expression of inducible NO synthase (iNOS) and tumor necrosis factor-α (TNF-α), as analyzed by RT-PCR and real-time PCR. Interestingly, KTH-13-AD1 strongly diminished NF-κB-mediated luciferase activities and nuclear translocation of NF-κB family proteins. In accordance, KTH-13-AD1 suppressed the upstream signaling pathway of NF-κB activation, including IκBα, IKKα/β, AKT, p85/PI3K, and Src in a time- and dose-dependent manner. The autophosphorylation of Src and NF-κB observed during the overexpression of Src was also suppressed by KTH-13-AD1. These results strongly suggest that KTH-13-AD1 has strong anti-inflammatory features mediated by suppression of the Src/NF-κB regulatory loop.